2011
DOI: 10.2215/cjn.04190510
|View full text |Cite
|
Sign up to set email alerts
|

Serum Iron Markers Are Inadequate for Guiding Iron Repletion in Chronic Kidney Disease

Abstract: Summary Background and objectives Iron (Fe) overload may complicate parenteral Fe therapy used to enhance the efficacy of erythropoietic-stimulating agents in the treatment of anemia of chronic kidney disease. However, serum Fe markers are influenced by inflammation or malignancy and may not accurately reflect the amount of body Fe. Design, setting, participants, & measurements We studied the relationship between parenteral Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 35 publications
8
128
4
4
Order By: Relevance
“…As described in a recent review, 9 use of IV iron preparations can increase the risk for infection, 10,11 cause oxidative stress, [12][13][14][15][16][17][18][19] promote cardiovascular disease, 11,[20][21][22][23][24] and lead to iron overload. [25][26][27][28] In addition, some IV iron preparations cause life-threatening anaphylactic reactions in susceptible individuals.…”
mentioning
confidence: 99%
“…As described in a recent review, 9 use of IV iron preparations can increase the risk for infection, 10,11 cause oxidative stress, [12][13][14][15][16][17][18][19] promote cardiovascular disease, 11,[20][21][22][23][24] and lead to iron overload. [25][26][27][28] In addition, some IV iron preparations cause life-threatening anaphylactic reactions in susceptible individuals.…”
mentioning
confidence: 99%
“…They further showed that serum ferritin values exceeding 340 µg/L were associated with iron overload. Similarly Ferrari et al 72 and Rostoker et al 73 recently showed a dramatic increase of liver iron contents approaching those found in hemochromatosis with routine administration of IV iron preparations in hemodialysis patients. It thus is clear that iron overload commonly occurs in ESRD patients treated with ESAs and IV iron according to the currently accepted guidelines.…”
Section: Potential Adverse Effects Of IV Iron On the Livermentioning
confidence: 73%
“…Of note, no cardiac iron deposits were observed by T2* in either study [61,62]. Thus, most hemodialysis patients receiving ESA and IV iron supplementation according to current guidelines appear to have hepatic iron overload in these recent LIC imaging studies [8,11,[59][60][61][62]. Whereas the potential iron overload toxicity is now one of the most controversial topics in the management of anemia in hemodialysis patients, data on this topic are lacking in peritoneal dialysis patients.…”
Section: Noninvasive Imaging Of Liver Iron Stores By Mri: Specific Fementioning
confidence: 99%
“…Radiologists and nephrologists should realize that there are marked differences in the pharmacokinetics of IV iron products, and that these can interfere with MRI (tables II and III) [57]. The required time interval between the last IV iron infusion and MRI should range from one week (iron sucrose, iron gluconate, iron carboxymaltose) to one month (low-molecularweight iron dextran and iron isomaltoside), 3 months (highmolecular-weight iron dextran) or even 6 months (ferumoxytol) if spurious results due to magnetic interference are to be avoided ( Iron overload in dialysis patients in the ESA era Studies using superconducting quantum interference device (SQUID) thirteen years ago [11] and more recent studies employing quantitative MRI [8,59,60] to estimate LIC in hemodialysis patients, have provided new information on iron metabolism in ESRD and have underlined the risk of hemosiderosis. These studies also strongly suggest a link between the IV iron dose and the risk of iron overload in this setting, challenging current guidelines with respect to the influence on LIC of IV iron products at high repeated doses [4,8,17,18,59,60], as well as the reliability of iron biomarker cutoffs, and methods for monitoring iron stores in dialysis patients [8,9,15,16].…”
Section: Noninvasive Imaging Of Liver Iron Stores By Mri: Specific Fementioning
confidence: 99%
See 1 more Smart Citation